Malaysia’s educational efforts in Southern Africa: creating opportunities, developing partnerships - Muhammed Haron, (penerbit ukm, 2013)
During this era of globalization and over the past two decades which coincides with post-Cold War developments, the world has witnessed major transformations taking place in international relations on different levels. The Southern Africa communities have observed radical transformation in the educational system as well as changes in educational policies and structures elsewhere in the region. They have, for example, seen the establishment of new educational institutions such as branches of Lim Kok Wing University of Creative Technology (LUCT) in Botswana, Lesotho and Swaziland, and they witnessed the formation of educational partnerships between institutions such as the International Peace College (IPSA) of Southern Africa and the International Islamic University of Malaysia (IIUM). These developments have undoubtedly contributed towards empowering individuals from the region and this demonstrated the viability of creating new educational opportunities and educational partnerships that have thus far taken place between Malaysia’s educational institutions and Southern African communities. The essay’s purpose is to reflect upon Malaysia’s educational interventions in Southern Africa; it does so by (1) reflecting upon the IIUM’s educational partnership with the Cape Town based IPSA, (2) commenting on Dunia Melayu Dunia Islam’s (DMDI) language programme in Cape Town, and by (c) reviewing the Botswana based LUCT’s educational contributions in Botswana. Adopting a historical reflective approach and based upon the respective assessments and reviews, the essay’s findings underlined that these significant educational connections have created new academic opportunites for certain sectors of the Southern African communities; and since this the case the general conclusion is that academic interventions and partnerships can make a huge difference in educational development.